War time an idea, its history, its consequences - Dudziak, Mary L. (Oxford University Press, 2012)
"On the surface, "wartime" is a period of time in which a society is at war. But we now live in what President Obama has called "an age without surrender ceremonies," where it is no longer easy to distinguish between times of war and times of peace. In this inventive meditation on war, time, and the law, Mary Dudziak argues that wartime is not as discrete a time period as we like to think. Instead, America has been engaged in some form of ongoing overseas armed conflict for over a century. Meanwhile policy makers and the American public continue to view wars as exceptional events that eventually give way to normal peace times. This has two consequences: first, because war is thought to be exceptional, "wartime" remains a shorthand argument justifying extreme actions like torture and detention without trial; and second, ongoing warfare is enabled by the inattention of the American people. More disconnected than ever from the wars their nation is fighting, public disengagement leaves us without political restraints on the exercise of American war powers."--